Berry chemoprevention: Do berries decrease the window of opportunity for tumorigenesis. Issue 3 (20th July 2020) - May, Stephanie; Parry, Connor; Parry, Lee
Abstract: In addition to smoking and UV exposure, lifestyle factors, such as diet, nutrition, and physical activity, have been shown to play a significant role for many cancers. It is estimated that up to 50% of some cancer types are preventable; many through lifestyle and dietary changes with the presence or absence of certain dietary components strongly associated with an increased or decreased risk. Here we summarize the work that has been performed with polyphenols, with a focus on those derived from black raspberries. These have been extensively studied for the prevention and treatment of a variety of conditions and diseases. Here we focus on their use for the prevention or treatment of specific cancer types and the impact they have on biological systems. The aim is to highlight the need to improve our understanding of how the environment impacts upon the normal biological processes that affect health and disease, thereby, enabling us to implement smarter prevention and treatment measures. Abstract : A summary of the tumours and "hallmarks of cancer" that black raspberry polyphenols impact upon to elicit tumour suppressive effects.